Anterior Middle Chest Wall Reconstruction Using a Free Anterolateral Thigh Flap Resulted in Flail Chest: A Case Report. Issue 8 (August 2019) - Tsuge, Itaru; Saito, Susumu
Abstract : Supplemental Digital Content is available in the text.